2021
DOI: 10.3390/ijms222011167
|View full text |Cite
|
Sign up to set email alerts
|

Poly(amidoamine) Dendrimers as Nanocarriers for 5-Fluorouracil: Effectiveness of Complex Formation and Cytotoxicity Studies

Abstract: Two generations of positively charged poly(amidoamine) dendrimers (PAMAMs) were selected for study as potential carriers for the anticancer drug 5-fluorouracil (5FU), a drug primarily used in the treatment of colorectal cancer. Analytical techniques, such as UV-Vis spectrophotometry, NMR Spectroscopy and Laser Doppler Velocimetry (LDV), have shown that the most critical factor determining the formation of a PAMAM–5FU complex is the starting components’ protonation degree. The tests confirmed the system’s abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 49 publications
3
8
0
Order By: Relevance
“…In good agreement with the literature [37], these NMR findings are considered evidence for the host-guest interaction and, principally, the proximity of the guest molecule to the dendrimer surface, since only the chemical shifts of the terminal methylene protons of G4PAMAM were sensibly affected. This is in good agreement with the results of our previous study, where we demonstrated the effect of 5FU molecules on the zeta potential of the G4PAMAM dendrimer [15]. The higher drug attachment efficiency for the higher dendrimer/5FU molar ratio (1:100) resulted in a reduction in the zeta potential of the system value of approximately 22%.…”
Section: H Nmr Spectroscopysupporting
confidence: 92%
See 4 more Smart Citations
“…In good agreement with the literature [37], these NMR findings are considered evidence for the host-guest interaction and, principally, the proximity of the guest molecule to the dendrimer surface, since only the chemical shifts of the terminal methylene protons of G4PAMAM were sensibly affected. This is in good agreement with the results of our previous study, where we demonstrated the effect of 5FU molecules on the zeta potential of the G4PAMAM dendrimer [15]. The higher drug attachment efficiency for the higher dendrimer/5FU molar ratio (1:100) resulted in a reduction in the zeta potential of the system value of approximately 22%.…”
Section: H Nmr Spectroscopysupporting
confidence: 92%
“…Our previous studies, summarized in Figure 1, have shown that under properly optimized conditions, the G4PAMAM dendrimer binds approximately 20 molecules of 5FU, acting as a non-toxic and effective nanocarrier, in agreement with the literature [12,15]. While, so far, attention has been mainly focused on the binding efficiency of 5FU to the PAMAM or PEGylated PAMAM, there is a lack of studies investigating the localization of 5FU in the dendrimer structure.…”
Section: Introductionsupporting
confidence: 81%
See 3 more Smart Citations